2018
DOI: 10.1107/s2053229618007933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of N—H...S and N—H...π interactions inO,O′-diethylN-(2,4,6-trimethylphenyl)thiophosphate: a combination of X-ray crystallographic and theoretical studies

Abstract: In the crystal structure of O,O'-diethyl N-(2,4,6-trimethylphenyl)thiophosphate, CHNOPS, two symmetrically independent thiophosphoramide molecules are linked through N-H...S and N-H...π hydrogen bonds to form a noncentrosymmetric dimer, with Z' = 2. The strengths of the hydrogen bonds were evaluated using density functional theory (DFT) at the M06-2X level within the 6-311++G(d,p) basis set, and by considering the quantum theory of atoms in molecules (QTAIM). It was found that the N-H...S hydrogen bond is slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Approximately 91 hits have been reported in the Cambridge Structural Database (CSD, Version 5.39, November 2017 + 4 updates; Groom et al, 2016) (the restrictions being nondisordered, no-error, nonpolymeric systems) for the The concomitant occurrence of crystals of Forms I and II phosphoramidate skeleton and this shows that this class of compound has merely been explored in terms of crystal structure and polymorphism (Torabi Farkhani et al, 2018;Tarahhomi et al, 2013). With almost one million entries in the CSD, it provides a vast database to determine statistical trends in this class of solids.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 91 hits have been reported in the Cambridge Structural Database (CSD, Version 5.39, November 2017 + 4 updates; Groom et al, 2016) (the restrictions being nondisordered, no-error, nonpolymeric systems) for the The concomitant occurrence of crystals of Forms I and II phosphoramidate skeleton and this shows that this class of compound has merely been explored in terms of crystal structure and polymorphism (Torabi Farkhani et al, 2018;Tarahhomi et al, 2013). With almost one million entries in the CSD, it provides a vast database to determine statistical trends in this class of solids.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical calculations were also applied to an evaluation of N-HÁ Á ÁY P (Y = O and S) hydrogen-bond strengths, which in a typical N-HÁ Á ÁS P hydrogen bond examined is about one-half with respect to N-HÁ Á ÁO P, e.g. 4.00 kcal mol À1 (1 kcal mol À1 = 4.184 kJ mol À1 ) in [2,4,6-(CH 3 ) 3 C 6 H 2 NH]P(S)[OCH 2 CH 3 ] 2 (Torabi Farkhani et al, 2018) and 6.99 kcal mol À1 in [(4-CH 3 O)C 6 H 4 C(O)NH]-P(O)[NHCH 2 C 6 H 4 (4-CH 3 )] 2 (Taherzadeh et al, 2017). Furthermore, Shainyan et al (2010) reported the calculated hydrogen-bond energies for N-HÁ Á ÁS and N-HÁ Á ÁO within the ranges 3.8-6.0 and 4.8-8.6 kcal mol À1 , respectively, for some sulfonamide derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[CSD refcodes LEQRIK/LEQRIK01 (Gholivand et al, 2013) and HOBSID/HOBSID01 (Hasija & Chopra, 2019)]. On exploring more, derivatives of phosphoric acid have been unraveled, where the study encompasses the detailed investigation of the crystalline arrangement via the presence of different intermolecular interactions (DuPlessis et al, 1982;Tarahhomi et al, 2012Tarahhomi et al, , 2013Hamzehee et al, 2016;Farkhani et al, 2018;Taherzadeh et al, 2021).…”
Section: Cambridge Structural Database Analysismentioning
confidence: 99%